Modern crop protection compounds (Wiley-VCH, 2007)
This set of books address all important aspects form the history to the mode of action, from the effects on the organism to major commercial products and their industrial synthesis. Following an introduction, individual sections cover herbicides including plant growth regulators, fungicides and insecticides. A series of special chapters in new research methods cover hot topics such as high throughput screening in mordern agro-chemical research, the role of fluorine and consequences for mordern drug design